The multicultural riddle : rethinking national, ethnic, and religious identities - Baumann, Gerd (Routledge, 1999)
A comprehensive exploration of all the issues that shape our search for a multicultural society.
Keywords: Ethnicity.; Multiculturalism.; Human rights.; Civil rights.; Religion and culture.; Human Rights; Civil Rights; Ethnicité.; Multiculturalisme.; Droits économiques et sociaux.; Droits de l'homme.; Religion et culture.; Droits de l'homme (Droit international); ethnicity.; multiculturalism.; civil rights.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Civil rights; Ethnicity; Human rights; Multiculturalism; Religion and culture; Etnische identiteit.; Godsdienst.; Multiculturele samenlevingen.